ESTIMASI TEGANGAN OPEN CIRCUIT DAN RESISTANSI INTERNAL BATERAI MENGGUNAKAN ALGORITMA RECURSIVE LEAST SQUARES - Topan, Paris Ali; Fardila, Dinda (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
This study employs the Recursive Least Squares (RLS) algorithm to estimate the Open Circuit Voltage (OCV) and internal resistance (Ro) of a battery in real-time, based on measured current and voltage data. The results demonstrate that RLS can produce accurate estimates of OCV and Ro, with a Mean Squared Error (MSE) of 0.031, indicating a very small difference between the predicted and measured terminal voltage. The estimated OCV is stable, while Ro remains consistently within the range of 0.075 to 0.175 ohms, despite fluctuations in voltage due to changes in current. These findings show that the RLS algorithm can be effectively applied in battery management systems to dynamically and in real-time estimate parameters, which is crucial for applications such as electric vehicle battery monitoring and energy storage systems.